Water infrastructure in Central Asia: legal and institutional frameworks - Ziganshina, Dinara (Frontiers in Climate, 2023)
This article examines existing arrangements for the operation, maintenance and construction of water infrastructure of interstate use in Central Asia. The Central Asian countries take diverse approaches to joint management of key water infrastructure of interstate use, with some country owned facilities operated by regional organizations, some owned and operated by the country of location with operation and maintenance cost shared with another country and others owned, operated and funded by the country other than country of location. This diversity is due to the need to accommodate to new political, socio-economic and technical circumstances after gaining independence in 1992. The findings suggest that achievements on coordinated management of water infrastructure largely built in the Soviet time should be further strengthened in terms of better financial and technical mechanisms. It is also important to agree on region-specific provisions on prior notification procedures in cases of proposed use on transboundary rivers that might have a transboundary impact and on the joint and mutually beneficial construction of new facilities of interstate use.